Introducing N‐Heteroaromatic Bases into Copper(II) Thiosemicarbazon Complexes: A Way to Change their Biological Activity. Issue 12 (21st December 2022) - Ulchina, Ianina; Graur, Vasilii; Tsapkov, Victor; Chumakov, Yurii; Garbuz, Olga; Burduniuc, Olga; Ceban, Emil; Gulea, Aurelian
Abstract: Three new copper(II) complexes, [Cu(1, 10‐Phen)(L)] (1 ), [Cu(2, 2′‐Bpy)(L)] (2 ) and [Cu(3, 4‐Lut)(L)] (3 ), where H2 L=2‐[(2, 4‐dihydroxyphenyl)methylidene]‐ N ‐(prop‐2‐en‐1‐yl)hydrazine‐1‐carbothioamide, 1, 10‐Phen=1, 10‐phenanthroline, 2, 2′‐Bpy=2, 2′‐bipyridine, 3, 4‐Lut=3, 4‐lutidine, have been synthesized and characterized by elemental analysis, FTIR spectroscopy and single crystal X‐ray crystallography (1, 2 ). All compounds are mononuclear. The introduction of a monodentate N ‐heteroaromatic base (3, 4‐dimethylpyridine) has led to a significant increase of antimicrobial activity against Gram‐negative Escherichia coli and antifungal activity against Candida albicans compared to the pro‐ligand and the precursor complex [Cu(L)H2 O]. The introduction of bidentate N ‐heteroaromatic bases did not lead to such increase of antimicrobial and antifungal activities. Moreover, complex 3 surpasses the inhibitory activity of tetracycline toward Enterobacter cloacae and the inhibitory activity of fluconazole toward Candida parapsilosis and Cryptococcus neoformans . The study of antioxidant activity against cation radicals ABTS⋅ + showed that complexes 1 –3 are more active than Trolox, but only introduction of the monodentate N ‐heteroaromatic base (3, 4‐dimethylpyridine) led to the increase of antioxidant properties compared to the precursor complex. Abstract : 3, 4‐Dimethylpyridine strengthening copper(II) : Three copper(II) complexes of 2‐[(2, 4‐dihydroxyphenyl)methylidene]‐ N ‐(prop‐2‐en‐1‐yl)hydrazine‐1‐carbothioamide and N ‐heteroaromatic bases were synthesized and studied by elemental analysis, FTIR spectroscopy and single crystal X‐ray crystallography. The study of antimicrobial, antifungal and antioxidant activities showed that the most active one is the copper(II) complex with 3, 4‐dimethylpyridine in the inner sphere.